Assessment of the supplied water quality for Sulaimani, Iraq as a case study using CCME method - Muhammed, Akber S.; Hama, Ako Rashed (Sulaimani Journal for Engineering Sciences, 2022)
Water quality index (WQI) is an important technique used for the evaluating and classifying water quality of supplied water, by summarizing large number of parameters from the result of variety tests of water into less number and terms Water quality index (WQI) value can be determined. Management of water quality is not so easy and simple, it needs to work with a lot of data. In this study evaluating of water quality of (Sulaimani city, KR, Iraq) is presented by using Canadian Council of Ministers of the Environment (CCME). The study conducted by monitoring long term water quality data over past eleven years, collected from 17 sampling points, tanks from which potable water supplied to all of the city residents, located in the (Sulaimani city, KR, Iraq). To obtain the CCME WQI value twelve parameters used : PH, Total dissolved solid (TDS), Chloride (Cl-1), Calcium (Ca), Sodium (Na), Potassium (K), Magnesium (Mg), Total hardness (TH), Total Alkalinity, Chloride (Cl2), Electric conductivity (EC), Sulphate (SO4-2).The obtained patterns present different water quality situations, WQI values ranged from good to excellent, based on the result obtained and analyzed using the from of WQI, it is revealed that the value of WQI ranged from (82) to (94) over the past 11 years, it means the main source of water supplied to the city which is Dokan lake is relatively high and clean as it is over a mountain watershed area.
Keywords: Assessment; CCME WQI; Water quality Guideline; Sulaimania city